Toward a spirit-led orthopathy of Pentecostal mission: Simultaneous vectors - Zarns, Phil (The journal of the European Pentecostal Theological Association, 2021)
A biblical orthodoxy and orthopraxy of mission considers the correct teaching and practice of evangelistic mission to provide access to the gospel for all nations. In keeping with right teaching and practice, this article endeavours to highlight a biblical orthopathy (right concern) of mission that considers the Spirit’s guidance amid the missionary task. Luke’s consistent inclusion of the term Holy Spirit in the narrative of the early church places a heightened value on an orthopathy of mission that focuses on obedience to the guidance of the Spirit in fulfilling the Great Commission. Discernment of the Spirit’s guidance in mission benefits current missiologies focused on unreached people groups.